CT-Scan Findings of Orbital Mass Among Pediatric Patients at a Tertiary Care Hospital in Bangladesh - Rahman, Meher Angez; Azad, Salauddin Al; Islam, Nazrul; Amin, Sadrul; Haque, Md ziaul; Kamal, Mahmud Hasan Mostofa; Mukhdira, - (Anwer Khan Modern Medical College Journal, 2017)
Background: CT-Scan for the detection of orbital mass among pediatric patients is very important noninvasive radiological modality. The purpose of the study was to find out CT-Scan findings of orbital mass among pediatric patients in a tertiary care hospital. Methodology: This is a cross sectional study was carried out in Ophthalmology and Radiology and Imaging department of National Institute of Ophthalmology (NIO) from January 2012 to December 2013. All the patient below 18 years of age presented with suspected orbital mass at Ophthalmology and Radiology and Imaging department of NIO and performed CT- Scan of orbit for diagnosis of the disease and also done histopathology after operation was enrolled in this study. Results: In this study it was observed that a total of 29 cases identified as malignant evaluated by CT, among them 27 cases were true positive and 2 cases were false positive. Benign was found in 41 cases evaluated by CT scan, out of which 1 false negative and 40 cases were true negative. The sensitivity in diagnosis of orbital tumor by CT was 93.3%. Conclusion: The sensitivity in diagnosis of orbital tumor by CT was high and is a useful method in the differentiation between benign and malignant orbital mass. Anwer Khan Modern Medical College Journal Vol. 8, No. 1: Jan 2017, P 17-23